Realizing Lobe-Specific Aerosol Targeting in a 3D-Printed In Vitro Lung Model - Kolewe, Emily L.; Feng, Yu; Fromen, Catherine A. (Journal of aerosol medicine and pulmonary drug delivery, 2021)
Delivery of aerosols to isolated lobes of the lungs would be beneficial for diseases that have lobe-specific effects, such as cancer, pneumonia, and chronic obstructive pulmonary disorder. Recent computational fluid-particle dynamic (CFPD) modeling has demonstrated that in low flow rates, the inlet location of a particle at the mouth dictates the lobe into which it will deposit. However, realization of this lobe-specific deposition has yet to be attempted experimentally or in the clinic. To address this, we sought to develop a proof-of-concept model and targeting device for achieving lobe-specific delivery. Using 3D printing, a lung replica was created from a computed tomography scan of a healthy 47-year-old male volunteer and connected to a flow setup to control inlet flow rate and outlet airflow distribution to each lobe. A device was designed and fabricated that directs particles to an inlet location that is 5% of the total inlet area and described by radial coordinates ( , ). Filter paper at sampling ports for each lobe was used to capture fluorescent polystyrene particles to quantify particle collection. We evaluated lobe-specific targeting at varied inlet coordinates, particle diameters, inlet flow rates, and disease lobe flow rate distribution profiles. Guided by CFPD modeling, inlet locations were identified that increased particle collection to a target lobe between 63% and 90%. For example, release of fluorescent particles at the inlet location = 4.67 mm, = 252° with respect to the center of the inlet using 1 μm particles, 1 L/min inlet flow rate, and healthy subject lobe flow distribution profile yielded 90% of the aerosol dose to the right upper lobe, corresponding to an increase of 4.6 × above the non-targeted percent particle collection. Particle size, inlet flow rate, and disease airflow distributions were all shown to generally decrease the efficiency of lobe-specific targeting. Our results indicate that aerosol targeting of a specific lobe is possible under optimized conditions and that controlling inlet locations could be a potentially useful method for treatment of lobe-specific diseases. This is the first demonstration of lobe-specific particle collection in a physical lung model and illuminates numerous challenges that will be faced as this method is translated to clinical applications.